2001
DOI: 10.1038/90034
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of POLG is associated with progressive external ophthalmoplegia characterized by mtDNA deletions

Abstract: Progressive external ophthalmoplegias (PEO) characterized by accumulation of large-scale mitochondrial DNA (mtDNA) deletions are rare human diseases. We mapped a new locus for dominant PEO at 15q22-q26 in a Belgian pedigree and identified a heterozygous mutation (Y955C) in the polymerase motif B of the mtDNA polymerase gamma (POLG). We identified three additional POLG missense mutations compatible with recessive PEO In two nuclear families. POLG is the only DNA polymerase responsible for mtDNA replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
479
1
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(493 citation statements)
references
References 17 publications
4
479
1
9
Order By: Relevance
“…Direct sequencing of the complete coding region and the exon/intron boundaries of the candidate genes POLG, 3 POLG2, 4 C10orf2 (Twinkle),5 SLC25A4 (ANT1),7 OPA1, 17 PINK1, 29 and PARK2 30 were carried out as previously described. Large gene deletions or duplications in PARK2 and PINK1 genes were tested by using the MLPA assay for Parkinson disease (SALSA MLPA Kit P051/P052 Parkinson; MRC‐Holland, Amsterdam, the Netherlands).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct sequencing of the complete coding region and the exon/intron boundaries of the candidate genes POLG, 3 POLG2, 4 C10orf2 (Twinkle),5 SLC25A4 (ANT1),7 OPA1, 17 PINK1, 29 and PARK2 30 were carried out as previously described. Large gene deletions or duplications in PARK2 and PINK1 genes were tested by using the MLPA assay for Parkinson disease (SALSA MLPA Kit P051/P052 Parkinson; MRC‐Holland, Amsterdam, the Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Most of these cases are caused by mutations in nuclear genes directly involved in mtDNA replication and maintenance, that is, POLG 3 and POLG2 ,4 encoding the 2 subunits of mtDNA polymerase, C10orf2 ,5 encoding the mtDNA helicase Twinkle, and DNA2 ,6 encoding an mtDNA helicase/nuclease. Mutations in genes that control the mitochondrial nucleotide pools can also be associated with this phenotype, including SLC25A4 ,7 encoding the heart/muscle‐specific adenine nucleotide translocator ANT1, TYMP ,8 encoding thymidine phosphorylase, TK2 ,9 encoding the mitochondrial thymidine kinase, RRM2B ,10 encoding the p53‐sensitive subunit of ribonucleoside reductase, and DGUOK ,11 encoding mitochondrial deoxyguanosine kinase.…”
mentioning
confidence: 99%
“…POLG1 was downregulated in patients ( Figure 1). POLG1 is one of the causative genes for mitochondrial diseases, such as chronic progressive ophthalmoplegia 35 and mitochondrial recessive ataxia syndrome, 36 both of which frequently comorbid with mood disorders. We showed that transgenic mice with neuron-specific expression of mutant Polg1 displayed BD-like phenotypes.…”
Section: Biomarkers Of Bipolar Disorder T Kato Et Almentioning
confidence: 99%
“…Although the specific function of the conserved spacer sequences is not known, a missense mutation in the spacer region of Drosophila pol ␥-␣ causes mitochondrial and nervous system dysfunction and developmental lethality in the larval third instar (24). Furthermore, hereditary progressive external ophthalmoplegia is associated with mutations in human pol ␥-␣, some of which map to the spacer region (5,25,26).Here we examine the consequences of site-directed mutagenesis of conserved amino acid sequences in the spacer region of Drosophila pol ␥-␣. Mutant holoenzymes were expressed from baculovirus constructs in insect cells, purified to near homogeneity, and characterized biochemically.…”
mentioning
confidence: 99%